Potential Mechanisms of SGLT2 Inhibitors for the Treatment of Heart Failure With Preserved Ejection Fraction - Pabel, Steffen; Hamdani, Nazha; Singh, Jagdeep; Sossalla, Samuel (Frontiers in Physiology, 2021)
Heart failure with preserved ejection fraction (HFpEF) is an unsolved and growing concern in cardiovascular medicine. While no treatment options that improve prognosis in HFpEF patients has been established so far, SGLT2 inhibitors (SGLT2i) are currently being investigated for the treatment of HFpEF patients. SGLT2i have already been shown to mitigate comorbidities associated with HFpEF such as type 2 diabetes and chronic renal disease, however, more recently there has been evidence that they may also directly improve diastolic function. In this article, we discuss some potential beneficial mechanisms of SGLT2i in the pathophysiology of HFpEF with focus on contractile function.